Fisioterapi Dada terhadap Hemodinamik dan Saturasi Oksigen pada Anak dengan Pneumonia - Damayanti Polapa; Nyimas Heny Purwanti; Anita Apriliawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of chest physiotherapy on hemodynamics (RR and HR) and oxygen saturation of children with pneumonia at Anutapura Hospital, Palu. This research uses quantitative research methods with this type of research using a quasi-experimental method with a two-group pre-post-intervention design. The results showed an effect of chest physiotherapy on hemodynamic status (HR and RR) and oxygen saturation in children with pneumonia at Anutapura Hospital, Palu, with a p-value <0.05. In conclusion, there is a significant effect of implementing chest physiotherapy interventions on hemodynamic status (HR and RR) and oxygen saturation in children with pneumonia at Anutapura General Hospital, Palu Keywords: Toddlers, Chest Physiotherapy, Hemodynamics, Pneumonia, Oxygen Saturation